Recommendations for regional policy: the Croatian case - Zlatan Fröhlich; Sanja Malekovic (European Regional Science Association (ERSA), 2004)
The regional differences in entrepreneurial activity are only one manifestation of the large regional differences in Croatia. From this it is obvious that Croatia needs regional policy as a part of its overall development policy. Contemporary regional policy gives strategic importance to industrial restructuring and other structural adjustments in regions that lag in development. However, it is not limited to relatively undeveloped regions, since rich regions can create demand that can “pull” growth in relatively less developed regions. A limitation on the implementation of modern regional policy in Croatia is the inherited doctrine of the reconstruction of war affected areas. This doctrine is no longer appropriate to the needs of new regional policy, which must be formulated in the context of EU accession. This is especially important considering that the EU emphasizes that member states must be in a position to withstand competitive pressures in the single market as a key condition for accession. And regional policy has a special role in this. The next limitation lies in the strong sectoral rather than integral approach. This is best seen in the many uncoordinated actions of various ministries and other government bodies. Furthermore, the legal framework is highly compartmentalized, so that Croatia does not have a single legal act that systematically regulates regional development on the whole territory of Croatia. Finally, the greatest limitation lies in the low level of ability of public administration, which is particular deficient in regional planning, programming and evaluating the implementation of development programs. These problems can be overcome through the following four goals of regional policy, which will be as recommendations discussed in the paper: - Reach national cohesion and sustainable development of local and regional communities. - Develop human resources with the aim of maintaining the population by opening prospects for work and employment. - Preserve urban, rural and littoral space, value it and using it optimally - Develop competitive, restructured sectors with special emphasis on the development of small and medium enterprises and the entrepreneurial environment.
Keywords: 330